Vol.1 - "Chandrasekhar, C.P." (Hyderabad, 2006)
The first of a two-part series, this volume and its sequel are compendia of interesting and well-researched articles that were first published in the fortnightly column MicroScan, in The Hindu Business Line. The articles in this volume have been arranged chronologically and thematically, spanning the period 2001-2005. They discuss several aspects of macroeconomy. The ideas and analyses contained in this book have been developed on the basis of the authors close interactions with Prabhat Patnaik and Abhijit Sen. The second of this two-part series on macroeconomy, this volume is co-authored by CP Chandrasekhar, Professor, Centre for Economic Studies and Planning, Jawaharlal Nehru University, New Delhi and Jayati Ghosh, Professor of Economics and chairperson, Centre for Economic Studies and Planning, School of Social Sciences, Jawaharlal Nehru University, New Delhi. This volume deals with international economic issues and is based in the 9/11 period. It also discusses the power of US multinational companies, Japans declining economy, and Afghanistans post-war economy.
Keywords: Macroeconomics